The European Union / History, Institutions, Economics and Policies - Agraa-El M. Ali (Prentice Hall Europe, 1998)
A comprehensive guide to the history, institutions, economic, and policies of the European Union. Preface, List of Abbreviations, General Introduction, Historical and Institutional and Statistical Background, History and Institutions of the EU, The Basic Statistics of the EU, Theory and Measurement, The Theory of Economic Integration, European Monetary Integration, Measuring the Impact of Economic Integration, The Economics of the Single Market, Major EU Policies, EU Competition Policy, EU Industrial Policy, The Common Agricultural Policy, The Common Fisheries Policy, EU Transport Policy, EU Energy Policy, Tax Harmonization, The General Budget, The European Monetary System, EU Regional Policy, EU Social Policies, EU Environmental Policy, Factor Mobility, EU External Trade Policy, The Lome Agreement, EU Enlargement, Conclusions, The Development of the EU, The Future of the EU.